Utilização de CO2 supercrítico e ácidos orgânicos na lixiviação de índio presente em telas de lcd de telefones celulares - Argenta, Aline Brum (2015)
The growth in the generation of electrical and electronic equipment waste (WEEE) has won global importance and cell phones are highlighted between these wastes because of short life cycle and its amounts of hazardous materials. In LCD screens, there is a mixture of indium tin oxide (ITO), typically tin oxide (10-20 %) and indium oxide (80-90 %). The indium (In) is a metal of relatively limited resources and has extensive use. Thus, this work aims to obtain an effective method for extraction of In from LCD screens of mobile phones. To this purpose, after manual separation of LCD screens followed by mechanical treatment, leaching at atmospheric pressure comparing the citric, malic and acetic acids, were carried out varying parameters like temperature, concentration of acid, solid:liquid ratio, volume peroxide hydrogen and reaction time. Therefore, the best conditions set out in the leaching at atmospheric pressure were used for extraction in supercritical CO2, where the employment of different temperatures and critical pressures were studied, in order to make the process faster and more efficient. The In concentration extracted in both cases was determined by atomic absorption (AAS). The extraction using 1M citric acid, 90 °C, 1:20 solid:liquid ratio with 5 % of the volume of H2O2 performed for 3 hours resulted in extraction of 76.5 % of In present in the LCD screens from obsolete cell phones. The leaching process using supercritical fluid in the presence of co-solvents, provided reduction in extraction time and higher percentage of metal extraction, reaching 90.2 % when were used 1 M citric acid, 80 °C, 1:20 ratio solid:liquid with 5 % v/v of H2O2, pressure of 150 bar and 30 minutes of process time. In order to transfer the obtained In in solution to a solid phase, the adsorption process was carried out with activated carbon and Spirulina as adsorbent, yielding removal 77.8 and 67.8 %, respectively. Thus, a new process for In recovery was developed, which in addition to reducing environmental pollution generated by the incorrect disposal of LCD screens of mobile phones and the employment of inorganic acids conventionally used, reduces the consumption of natural resources, making the promising process.